Seasonal frugivory drives both diet inconsistency and individual specialization in the generalist herbivore gopher tortoise - Figueroa, Adrian (2024)
Individual diet specialization, where individuals within a population exhibit distinct dietary patterns, can be influenced by shifts in ecological opportunity. One underexplored avenue of research is in investigating whether individuals switch foraging strategies (e.g., shifting from herbivory to frugivory) when ecological opportunity provides a pulse of limiting resources, such as fleshy fruits. This study investigates the influence of seasonal frugivory on diet consistency and specialization among generalist herbivores, specifically the gopher tortoise (Gopherus polyphemus), in southeastern Florida, USA. We hypothesized that increased frugivory during the wet season (June through November), coinciding with a resource pulse of fleshy fruits, leads to more inconsistent and specialized diets. Using radio telemetry to track individual tortoises and analyzing dissected fecal samples grouped into functional food categories, we applied Bayesian hierarchical modeling to examine diet consistency and specialization. Our results indicated that higher frugivory levels in the wet season correlate with greater diet inconsistency and specialization compared to the dry season. This pattern suggests that gopher tortoises may switch foraging strategies to exploit seasonal resource pulses of fleshy fruit, thus adopting more inconsistent and specialized diets. Additionally, important activities in the life history of the gopher tortoise, such as copulation, home range defense, and burrow construction, coincide with periods of increased fruit consumption and dietary inconsistency/specialization. Increased intake of carbohydrates and digestible energy from fleshy fruits may allow for more time in the tortoise's activity budget for these activities. Finally, by elucidating the relationship between seasonal frugivory and diet consistency/specialization, this research enhances our understanding of the mechanisms shaping ecological dynamics at the intraspecific level which can subsequently influence community-level interactions such as animal-mediated seed dispersal.